2014
DOI: 10.1007/s40279-014-0164-z
|View full text |Cite
|
Sign up to set email alerts
|

On-Court Demands of Elite Handball, with Special Reference to Playing Positions

Abstract: The aim of this review is to provide the first comprehensive analysis of the various technical and physical on-court demands in elite male handball with respect to playing positions. While low-intensity activities such as standing still and walking represent the greater proportion of playing time (up to ~70 %), handball can be considered an intense activity for all players, especially because of the large number of repeated high-intensity actions occurring throughout the game (e.g., jumps, sprints, changes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
347
1
18

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(385 citation statements)
references
References 60 publications
19
347
1
18
Order By: Relevance
“…Optimal performances in handball requires a high amount of explosive actions such as sprints, jumps and changes in direction during the game (Karcher & Buchheit, 2014). In our study, no significant differences have been found regarding variables involved in CMJ, in line with results obtained by Buchheit et al (2009) with young handball players, in which CMJ did not either develop after HIIT.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Optimal performances in handball requires a high amount of explosive actions such as sprints, jumps and changes in direction during the game (Karcher & Buchheit, 2014). In our study, no significant differences have been found regarding variables involved in CMJ, in line with results obtained by Buchheit et al (2009) with young handball players, in which CMJ did not either develop after HIIT.…”
Section: Discussionsupporting
confidence: 84%
“…These are considered to be the most significant actions to develop high performance (Bilge, 2013;Michalsik et al, 2013;Karcher & Buchheit, 2014;Iacono et al, 2015b). In their study on professional handball players, Povoas et al (2012) showed how athletes performed very short 825 actions (2-6 seconds) in a 73-minute game, investing a lot of energy in acceleration and deceleration.…”
Section: Introductionmentioning
confidence: 99%
“…Average running speed during handball game is lower than most other team games, including football. However, a relatively higher lactate concentration likely results from frequent jump, throw, and more body contact than many others [12]. The La values were also higher than most of the court games like basketball [13] or volleyball [14].…”
Section: -----------------------mentioning
confidence: 97%
“…Thereby, the external load is characterized by a total distance covered of 2.8 -4.4 km (3,4), mean velocity of 53 -90 m/min (3,5), sprinting distance of 78 -107 m (3,6), and peak velocity of 20 -25 km/h (2), whereas the internal demand is considered by a mean heart rate of 82% -83% (2, 3), peak lactate concentration of 3.7 -9.7 mmol/L (7,8), and fluid loss of 2.0 -2.1 L (3,8). Notably, all match play activities as well as external loads and internal demands differ not only according to playing positions (9), but also to offensive and defensive playing phases and tactical formations (1). 4).…”
Section: Introductionmentioning
confidence: 99%